(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Current in the day carbonate anhydride in sorption apply for research being done hard sorbents three big to the group to be possible: inorganic compounds and minerals, polymers and organic compounds, hybrid materials. Inorganic from compounds alkaline and alkaline land of meta oxides, hydroxides, peroxides is studied.